Universal characteristics of clip culture - A. P. Avdeeva; Yu. A. Safonova (Вестник университета)
The article analyzes the phenomenon of clip culture. Alvin Toffler’s information society dynamics concept has become the methodological basis of the research. The purpose of the study is to highlight the universal characteristics of clip culture considering the current state of the info- and technosphere. The following characteristics of clip culture have been identified: tempo and rhythm changes, mosaic of images, focus on visual and emotional components, formulaic narration, hypertextuality. The changes are the most visible in the media sphere. However, they are also observed in everyday life, manifested by the variety of choices, kaleidoscope of images, and fragmentation of life itself. The results of the study may be of interest to sociologists, culturologists, psychologists, as well as specialists in the field of education clarifying the cognitive needs of modern young people.